Radical Religious Communities : Internal Dynamism and Social Significance (14th-16th centuries) - Cermanová, Pavlín; Pjecha, Martin; Soukup,Pavel (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
The twenty-first century has demonstrated that radicalism remains a vital analytical concept in the study of modern religion and politics. However, its application to earlier periods has been met with more ambivalence. This volume challenges that trend by examining religio-political subversives near the close of the Middle Ages as radical within their historical and intellectual contexts, spanning several centuries and cultures, with a focus on Central Europe. In doing so, it seeks to bridge entrenched geographical, chronological, and methodological divides, fostering broader discussions on the comparative relevance of radicalism in pre-modernity.